Durability assessment of automotive structures under random variable amplitude loading. (April 2018) - Zhao, Li-Hui; Cai, Hong-Chang; Wang, Tong; Zheng, Song-Lin
Durability assessment is essential for assuring the reliability and safety of automotive structures, which subjects to complex random variable amplitude loadings. In this article, the application of different damage accumulation rules were discussed through the example of torsion beam rear axle from a sport utility vehicle, which is an assembly of welded thin sheet metals. Fatigue lives were calculated with these rules together with the structural stress at failure locations and the stress–life curve determined through the constant amplitude test of specially designed standard specimens stress distributions in the vicinity of failure locations. By comparing the calculated lives with test results, it is found that all the calculations with an stress–life curve for the probability of survival of Ps  = 50% are conservative compared to the experimental mean value even the 95% confidence interval, and that with linear damage accumulation hypothesis is of better estimate, followed by the damage curve approach, while the double-linear rule will result in the most conservative estimation. Moreover, the modified Miner Rule, which extends the stress–life curve with a flatter slope k ′ = 2 k  − 1 below the fatigue limit, is recommended for structural fatigue design for its appropriate estimations corresponding to a low failure rate with high confidence level.